Exploration of carboxy pyrazole derivatives: Synthesis, alkaline phosphatase, nucleotide pyrophosphatase/phosphodiesterase and nucleoside triphosphate diphosphohydrolase inhibition studies with potential anticancer profile - Channar, Pervaiz Ali (2018)
In the present work we report the synthesis of new aryl pyrazole derivatives using 1,3-dicarbonyl motifs. The reaction was proceeded by the cyclization of pentane-2,4-dione (1a), 3-chloropentane-2,4-dione (1b) or ethyl 3-oxobutanoate (1c) with different aryl hydrazines. The products, which can be regarded as 1H-pyrazol-1-yl-one analogues (3a-f, 3g-o, 4a-c, 5a-b) and represent drug like molecules along with well-developed structure?activity relationships, were obtained in good to excellent yield. The structures of synthesized compounds were charcterized on the basis of FT-IR, 1H NMR, 13C NMR and mass spectroscopic data. Considering alkaline phosphatases (APs), nucleotide pyrophosphatases/phosphodiesterases (NPPs) and nucleoside triphosphate diphosphohydrolase as the molecular targets, the effects of these synthesized compounds were investigated on different isozymes of APs, NPPs and NTPDases. The data revealed that the synthesized compounds inhibited both enzymes but most of them inhibited tissue non-specific alkaline phosphatase (TNAP) more selectively. The antitumor activity results indicated that the synthesized derivatives have strong inhibitory effects on the growth of selected cell lines from different tissues such as breast, bone marrow and cervix (MCF-7, K-562 and Hela) but with varying intensities. Moreover the binding mode of interactions were explained on the basis of molecular docking and in-silico studies.